Large CRISPR-Cas-induced deletions in the oxamniquine resistance locus of the human parasite Schistosoma mansoni [version 1; peer review: 2 approved] - Geetha Sankaranarayanan; Avril Coghlan; Patrick Driguez; Magda E. Lotkowska; Mandy Sanders; Nancy Holroyd; Alan Tracey; Matthew Berriman; Gabriel Rinaldi (Wellcome Open Research, 2020)
Background. At least 250 million people worldwide suffer from schistosomiasis, caused by Schistosoma worms. Genome sequences for several Schistosoma species are available, including a high-quality annotated reference for Schistosoma mansoni. There is a pressing need to develop a reliable functional toolkit to translate these data into new biological insights and targets for intervention. CRISPR-Cas9 was recently demonstrated for the first time in S. mansoni, to produce somatic mutations in the omega-1 (ω1) gene. Methods. We employed CRISPR-Cas9 to introduce somatic mutations in a second gene, SULT-OR, a sulfotransferase expressed in the parasitic stages of S. mansoni, in which mutations confer resistance to the drug oxamniquine. A 262-bp PCR product spanning the region targeted by the gRNA against SULT-OR was amplified, and mutations identified in it by high-throughput sequencing. Results. We found that 0.3-2.0% of aligned reads from CRISPR-Cas9-treated adult worms showed deletions spanning the predicted Cas9 cut site, compared to 0.1-0.2% for sporocysts, while deletions were extremely rare in eggs. The most common deletion observed in adults and sporocysts was a 34 bp-deletion directly upstream of the predicted cut site, but rarer deletions reaching as far as 102 bp upstream of the cut site were also detected. The CRISPR-Cas9-induced deletions, if homozygous, are predicted to cause resistance to oxamniquine by producing frameshifts, ablating SULT-OR transcription, or leading to mRNA degradation via the nonsense-mediated mRNA decay pathway. However, no SULT-OR knock down at the mRNA level was observed, presumably because the cells in which CRISPR-Cas9 did induce mutations represented a small fraction of all cells expressing SULT-OR. Conclusions. Further optimisation of CRISPR-Cas protocols for different developmental stages and particular cell types, including germline cells, will contribute to the generation of a homozygous knock-out in any gene of interest, and in particular the SULT-OR gene to derive an oxamniquine-resistant stable transgenic line.